Ontology Driven Web Data Extraction - Hazlinda, Ghazali (2004)

(untitled)
Data extraction from web document is becoming more popular and widely used for many tasks. The objective of this study is to develop web data extraction technique from IEEE Conference announcement website to search for important dates related to conference. At present, problems arise due to non-standardized and free format web document. Besides that, multiple terms can have same meaning. In this study, information from web pages were extracted and structured from the websites by using ontology and used XML document to store data. The web data extraction technique is developed using Cold Fusion 4.5 web programming language.